P-10=6p-6p

Simple and best practice solution for P-10=6p-6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P-10=6p-6p equation:



-10=6P-6P
We move all terms to the left:
-10-(6P-6P)=0
We add all the numbers together, and all the variables
-10-0=0
We add all the numbers together, and all the variables
-10!=0
There is no solution for this equation

See similar equations:

| X÷2+3y÷5-1÷2=0 | | 12x-6=3- | | -1/3(6h+15)=15 | | 2x^+8x+9=0 | | X/2+3y/5-1/2=0 | | 2n-25=-n-50 | | 4(2x-1)+3=6x-19 | | 5/6x2=4/5x3 | | 2n-16=-n-100 | | 15(2+k)=420 | | -9d=99 | | (x-3)/(4x+1)=0 | | 3(x-7)+5(x+4)=15 | | (x-3)/(4x-1)=0 | | 8-x/3=5/2 | | 45=4v-11 | | 4(2x-1)+3=6x-1 | | -11x+2x(x-3)+7x=5x-6 | | 4(2x-1)+3=6x-14 | | 13+2/3(x-8)+10x=7x=39 | | 1t-3/4=5/6 | | (y^2​-9)(y^2​​−4)=0 | | 10-(3z-4)=6-4z | | 12x-9=2x+63 | | y^2​​−9)(y^​2​​−4)=0 | | 6+12k=-10-4k | | y−4=5.4 | | 4(2x-1)+3=6x-17 | | 10n+35=28n+35 | | 11=v/4-14 | | 9+1/3+12=2y-6 | | 477=2b+3+4b+6+8b+12 |

Equations solver categories